Thermoelectric cooler ( tec ) for automotive cabin - Muhammad Khairulhariz, Md Zaki (2016)
Nowadays, air conditioning system of automobile arises to such many problems such as CFC emission that cause air pollution, the usage of fuel is increased and engine performance is decreased. Moreover, the current air-conditioning system is not capable to be used during the parked session. This scenario could be subdued by the introduction of thermoelectric device as an alternating cooling option for car interior. Fuel usage decrease by using this pollution option and decreased engine performance can be prevented since the letter option was in the bracket of ‘Go Green’ region. The project is to make the automotive cabin being cooled by using thermoelectric cooler that can be applied on the car in the hot sunny day. The system should be automatically turned on when the engine of the car is stop depending on the temperature inside and outside of the car. This temperature can be controlled by temperature sensor. The project is using the source of the automobile battery.